2012
DOI: 10.1111/j.1365-2133.2012.11178.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of general practitioners in diagnosis of cutaneous melanoma: a population‐based study in France

Abstract: GPs play a key role in melanoma diagnosis in France, but still frequently detect thick tumours. Increasing awareness and training of GPs and focusing attention on male and/or socially isolated patients should help to improve early detection of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…As reported by other authors, we observed that melanoma diagnosed in a GP setting were much thicker than those diagnosed in other healthcare settings (particularly by dermatologists) . However, we also demonstrated in this previous retrospective study that active detection by GPs (as opposed to detection by patients) was associated with a lower Breslow thickness and was improved by GP training . The present study extends these preliminary observations in France, by providing, for the first time, population‐based evidence that a systematic sensitization and training campaign for GPs may decrease the incidence of VTM and improve early diagnosis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As reported by other authors, we observed that melanoma diagnosed in a GP setting were much thicker than those diagnosed in other healthcare settings (particularly by dermatologists) . However, we also demonstrated in this previous retrospective study that active detection by GPs (as opposed to detection by patients) was associated with a lower Breslow thickness and was improved by GP training . The present study extends these preliminary observations in France, by providing, for the first time, population‐based evidence that a systematic sensitization and training campaign for GPs may decrease the incidence of VTM and improve early diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…most Americans do not have a dermatologist, few of them are screened for melanoma, most of them make frequent visits to their GP, most patients with melanoma have seen a physician in the year before diagnosis, many melanomas are not easily visible to patients), all are transposable to the French population and probably also to the populations of many developed countries. In France, a country counting 64 million inhabitants, 3400 dermatologists and 101 500 GPs at the beginning of the century, we recently brought to light an important decline in dermatologists as first medical caregivers to patients with melanoma between the years 2004 and 2008 . This may be explained both by an annual reduction in the number of dermatologists of about 6% since 2002, and by the modification of French legislation in 2004 which limited direct access to specialists, including dermatologists, and encouraged patients first to consult their referent GP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a pivotal role in melanoma detection, the melanomas they found were significantly thicker than those identified by other physicians (on average 2.05 mm versus 1.32 mm, p < 0.01) [22]. Collectively, these data suggest that primary care providers may benefit from additional training to facilitate earlier diagnosis of melanoma, especially among high-risk patients.…”
Section: Disclosuresmentioning
confidence: 71%
“…In this issue of the BJD , Florent Grange et al. 1 report on a vast population‐based study on the role of general practitioners (GPs) in 2008 in the diagnosis of cutaneous melanoma (CM) in north‐east France. Their main findings are instructive, even for non‐French readers.…”
mentioning
confidence: 99%